Freedom's trail - Bartlett, Richard A.; Keller, Clair W.; McKeever, Helen Carey (Boston : Houghton Mifflin, 1979)
This history textbook of the United States, from the first explorers to Carter's administration, pays particular attention to the contributions of women and minorities.
Includes index.
Keywords: United States -- History -- Juvenile literature; History